Fuzzy Logic-Based Arrival Time Estimation for Indoor Navigation Using Augmented Reality - Muhammad Hidayat Mohammed Sohif; Muhammad Imran Mardzuki; Azhar Mohd Ibrahim; Ahmad Jazlan (International Islamic University Malaysia Engineering Journal)
In recent years, Augmented Reality (AR) has gained popularity in various industries due to its ability to enhance efficiency, provide real-time information and data, and maintain user awareness of their surroundings. One of the applications of AR is in navigation, but most existing systems primarily focus on outdoor environments, neglecting indoor spaces. Mobile applications designed for indoor navigation often rely on expensive and computationally demanding beacons or natural markers to track the user's location along a predetermined path. Furthermore, traditional navigation estimation methods based on GPS are ineffective for indoor navigation. This study proposes a mobile AR application for indoor navigation that uses an intelligent signage algorithm based on fuzzy logic to estimate arrival time. The algorithm takes phone acceleration in the x and z directions as inputs and employs triangular-shaped membership functions for input and output variables. The experimental results indicate the feasibility of using fuzzy logic to estimate arrival time for indoor navigation, with an average prediction error of 5.82%.